Lipid droplet clearance inhibits esophageal cancer growth via metabolic reprogramming - Yan Pu; Yi Wan; Yuhua Fu; Kai Li; Yijiao Chen; Yunzhi Wang; Bin Li; Lingling Li; Zhaoyu Qin; Jingyan Xu; Dongxian Jiang; Yan Li; et al. (Science Bulletin, 2025)

Biomolecular condensates and disease pathogenesis - Ke Ruan; Ge Bai; Yanshan Fang; Dan Li; Tingting Li; Xingguo Liu; Boxun Lu; Qing Lu; Zhou Songyang; Shuguo Sun; Zheng Wang; Xin Zhang; et al. (Science China Life Sciences, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

Targeted clearance of mitochondria by an autophagy-tethering compound (ATTEC) and its potential therapeutic effects - Shuixia Tan; Da Wang; Yuhua Fu; Huiwen Zheng; Yan Liu; Boxun Lu (Science Bulletin, 2023)

Drugging “undruggable” neurodegenerative disease targets with small molecules - Junmei Lu; Zhaoyang Li; Aaron D. Gitler; Boxun Lu (Science Bulletin, 2023)

Autophagic Clearance of Lipid Droplets Alters Metabolic Phenotypes in a Genetic Obesity–Diabetes Mouse Model - Ningxie Chen; Boxun Lu; Yuhua Fu (Phenomics, 2023)
Lipid droplets (LDs) are intracellular organelles that store neutral lipids, and their aberrant accumulation is associated with many diseases including metabolic disorders such as obesity and diabetes. Meanwhile, the potential pathological contributions of LDs in these diseases are unclear, likely due to a lack of chemical biology tools to clear LDs. We recently developed LD-clearance small molecule compounds, Lipid Droplets·AuTophagy TEthering Compounds (LD·ATTECs), that are able to induce autophagic clearance of LDs in cells and in the liver of db/db (C57BL/6J Lepr db /Lepr db ) mouse model, which is a widely used genetic model for obesity–diabetes. Meanwhile, the potential effects on the metabolic phenotype remain to be elucidated. Here, using the metabolic cage assay and the blood glucose assay, we performed phenotypic characterization of the effects of the autophagic degradation of LDs by LD·ATTECs in the db/db mouse model. The study reveals that LD·ATTECs increased the oxygen uptake of mice and the release of carbon dioxide, enhanced the heat production of animals, partially enhanced the exercise during the dark phase, decreased the blood glucose level and improved insulin sensitivity. Collectively, the study characterized the metabolic phenotypes induced by LD·ATTECs in an obesity–diabetes mouse model, revealing novel functional impacts of autophagic clearance of LDs and providing insights into LD biology and obesity–diabetes pathogenesis from the phenotypic perspective.

Correction: Inhibition of HIPK3 by AST487 Ameliorates Mutant HTT-Induced Neurotoxicity and Apoptosis via Enhanced Autophagy - Xiaodan Zhang; Xue Wen; Ismael Al-Ramahi; Juan Botas; Boxun Lu; Yuhua Fu (Neuroscience Bulletin, 2022)

Inhibition of HIPK3 by AST487 Ameliorates Mutant HTT-Induced Neurotoxicity and Apoptosis via Enhanced Autophagy - Xiaodan Zhang; Xue Wen; Ismael Al-Ramahi; Juan Botas; Boxun Lu; Yuhua Fu (Neuroscience Bulletin, 2022)

Degeneration Versus Development: Hunting-Out the D-Unit of Huntington’s Disease - Shengyi Lu; Boxun Lu (Neuroscience Bulletin, 2021)

Modeling the Degradation Effects of Autophagosome Tethering Compounds - Hang Zhang; Ping An; Yiyan Fei; Boxun Lu (Neuroscience Bulletin, 2021)

Tau Accumulation via Reduced Autophagy Mediates GGGGCC Repeat Expansion-Induced Neurodegeneration in Drosophila Model of ALS - Xue Wen; Ping An; Hexuan Li; Zijian Zhou; Yimin Sun; Jian Wang; Lixiang Ma; Boxun Lu (Neuroscience Bulletin, 2020)